Development of Herbal Tea Bags using Gotu Kola Leaves (Centella asiatica L. Urban) and Siamese Orange Peel (Citrus nobilis) - Sylvi, Diana; Refdi, Cesar Welya; Dewi, Sesi Kumala (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
Herbal tea is a beverage made from dried leaves, flowers, seeds, nuts, bark, fruits, and other plant components, excluding Camellia sinensis. This study developed herbal tea bags using gotu kola leaves (Centella asiatica) and Siamese orange peel (Citrus nobilis) sweetened with stevia to enhance flavor and antioxidants. The research aimed to assess the chemical and organoleptic characteristics and identify the most preferred formula. Treatments involved varying ratios of gotu kola leaves to Siamese orange peel: (100%: 0%), (80%: 20%), (75%: 25%), (70%: 30%), and (65%: 35%). A Completely Randomized Design (CRD) with five treatments and three replications was used, and data were analyzed using ANOVA and DNMRT at a 5% significance level. Results showed significant effects of mixing ratios on DPPH antioxidant activity, total polyphenols, water-soluble content, pH, IC50 antioxidant activity, and organoleptic attributes (color and aroma), but not on moisture content, ash content, TPC, or taste. Treatment E (65%: 35%) was optimal, with moisture content 7.54%, ash content 6.65%, DPPH antioxidant activity 58.02%, total polyphenols 746.67 mg GAE/g, water-soluble content 35.33%, TPC 2.8Ã—10Â³ CFU/g, pH 6.71, and IC50 67 ppm. Panelists preferred this formulation, scoring its color (3.96), aroma (3.72), and taste (3.72) as "like".